Effect of a Novel Nonviral Gene Delivery of BMP-2 on Bone Healing. (11th November 2012) - Schwabe, P.; Greiner, S.; Ganzert, R.; Eberhart, J.; Dähn, K.; Stemberger, A.; Plank, C.; Schmidmaier, G.; Wildemann, B.
Abstract : Background. Gene therapeutic drug delivery approaches have been introduced to improve the efficiency of growth factors at the site of interest. This study investigated the efficacy and safety of a new nonviral copolymer-protected gene vector (COPROG) for the stimulation of bone healing. Methods. In vitro, rat osteoblasts were transfected with COPROG + luciferase plasmid or COPROG + hBMP-2 plasmid. In vivo, rat tibial fractures were intramedullary stabilized with uncoated versus COPROG+hBMP-2-plasmid-coated titanium K-wires. The tibiae were prepared for biomechanical and histological analyses at days 28 and 42 and for transfection/safety study at days 2, 4, 7, 28, and 42. Results. In vitro results showed luciferase expression until day 21, and hBMP-2-protein was measured from day 2 – day 10. In vivo, the local application of hBMP-2-plasmid showed a significantly higher maximum load after 42 days compared to that in the control. The histomorphometric analysis revealed a significantly less mineralized periosteal callus area in the BMP-2 group compared to the control at day 28. The rt-PCR showed no systemic biodistribution of luciferase RNA. Conclusion. A positive effect on fracture healing by nonviral BMP-2 plasmid application from COPROG-coated implants could be shown in this study; however, the effect of the vector may be improved with higher plasmid concentrations. Transfection showed no biodistribution to distant organs and was considered to be safe.